Allergen-specific Immunotherapy for Inhalant Allergens in Children - Caffarelli, Carlo; Cangemi, Jessica; Mastrorilli, Carla; Giannetti, Arianna; Ricci, Giampaolo (Current Pediatric Reviews, 2020)
Allergen-specific immunotherapy (AIT) for aeroallergens consists of the administration of standardized allergen extracts to patients with respiratory IgE-mediated diseases to the same allergen in order to achieve immune tolerance to the allergen and prevent the onset of symptoms. AIT is usually delivered by sublingual (SLIT), subcutaneous (SCIT) route. AIT with one or multiple allergens currently represents the only causal treatment able to change the natural history of allergic airway diseases. Significant progresses have been made in terms of AIT efficacy and safety. In this paper, mechanisms of action, indication and side effects of allergen immunotherapy are reviewed. SLIT and SCIT have been found to be effective in the treatment of asthma and rhinoconjunctivitis due to inhalant allergens. The route of AIT administration should be selected on availability, cost (dependent from the local health system), tolerability (better for SLIT), patient’s preference (injections are less accepted in young children), and adherence (higher for SCIT beyond pediatric age). However, it should be taken into account that metanalyses on AIT do not consider that effectiveness and safety depend upon the product chosen for treatment. Each product should be separately assessed to avoid generalization on administration routes or age group that may affect the decision.
Keywords: immunotherapy